A novel gold marker to aid intraoperative localisation during spinal surgery!. (3rd May 2020) - Dhahri, Prince A.; McCreary, R.; George, K. Joshi
Abstract: Methods of pre-operative level marking for spinal surgery include fiducial implants, coil implants, spinal needle implant, methylene blue and cement injection. We describe a novel gold marker used for preoperative spinal marking and report our experience. The notes and scans of patients who had gold marker for preoperative spinal marking over the period from June 2016 to November 2018 were analysed. 20 patients had preoperative spinal marking using the gold marker. The accuracy was 100% and there were no complications. Compared to injecting cement, we save over £700 per patient!